Natural Saccharomyces cerevisiae Strain Reveals Peculiar Genomic Traits for Starch-to-Bioethanol Production: the Design of an Amylolytic Consolidated Bioprocessing Yeast - Gronchi, Nicoletta; De Bernardini, Nicola; Cripwell, Rosemary A.; Treu, Laura; Campanaro, Stefano; Basaglia, Marina; Foulquié-Moreno, Maria R.; Thevelein, Johan M.; Van Zyl, Willem H.; Favaro, Lorenzo; Casella, Sergio (Frontiers in Microbiology, 2022)
Natural yeast with superior fermentative traits can serve as a platform for the development of recombinant strains that can be used to improve the sustainability of bioethanol production from starch. This process will benefit from a consolidated-bioprocessing (CBP) approach where an engineered strain producing amylases directly converts starch into ethanol. The yeast Saccharomyces cerevisiae L20, previously selected as outperforming the benchmark yeast Ethanol Red, was here subjected to a comparative genomic investigation using a dataset of industrial S. cerevisiae strains. Along with Ethanol Red, strain L20 was then engineered for the expression of α-amylase amyA and glucoamylase glaA genes from Aspergillus tubingensis by employing two different approaches (delta integration and CRISPR/Cas9). A correlation between the number of integrated copies and the hydrolytic abilities of the recombinants was investigated. L20 demonstrated important traits for the construction of a proficient CBP yeast. Despite showing a close relatedness to commercial wine yeast and the benchmark Ethanol Red, a unique profile of gene copy number variations (CNV) was found in L20, mainly encoding membrane transporters and secretion pathway proteins but also the fermentative metabolism. Moreover, the genome annotation disclosed 573 unique open reading frames (ORFs) that are absent in the reference S288C genome, where nearly half are involved in the processing of genetic information. Genome engineering was successfully implemented for amylase production. However, with equal amylase gene copies, L20 proved its proficiency as a good enzyme secretor by exhibiting a markedly higher amylolytic activity than Ethanol Red, in compliance to the findings of the genomic exploration. The recombinant L20 dT8 exhibited the highest amylolytic activity and produced more than 4 g/L of ethanol from 2% starch in a CBP setting without the addition of supplementary enzymes. Based on the performance of this strain, an amylase/glucoamylase ratio of 1:2.5 was suggested as baseline for further improvement of the CBP ability. Overall, L20 showed important traits for the future construction of a proficient CBP yeast. As such, this work shows that natural S. cerevisiae strains can be used for the expression of foreign secreted enzymes, paving the way to strain improvement for the starch-to-bioethanol route.